The Development of an Ecotourism-Based Tourism Village at Pemandian Rumah Putiah, Padang Pariaman Regency: Pengembangan Desa Wisata Berbasis Ekowisata di Pemandian Rumah Putiah Kabupaten Padang Pariaman - Deni Fadrian Putra; Aldri Frinaldi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Rumah Putiah Bath is a bathing pool sourced directly from mountain springs. The attraction of this Rumah Putiah bathing place is the clear and fresh water and the natural environment that is still beautiful and cool. The existing facilities are quite complete but poorly maintained such as dirty bathrooms, lots of scattered garbage and lack of human resources in managing them. The purpose of this research is to find out how the development carried out by the manager and what obstacles are faced in managing Rumah Putiah Bath. This research was conducted using a qualitative method by describing the data descriptively. Data collection techniques were carried out by observation, interviews and documents using qualitative descriptive analysis techniques. The results of the research obtained are that the development carried out at Rumah Putiah Bath is still not optimal because currently there is only one attraction, namely the bathing pool, access to the bathing location is still in the form of a damaged road and a parking lot that is still in the form of land. Factors inhibiting the development of Rumah Putiah Bathing Place tourism are the low human resources in managing this bathhouse, lack of community participation. In addition, land acquisition for additional pools and parking lots is not yet clear from the local government. The manager must pay more attention to the facilities in the bathhouse so that visitors are satisfied with the tour.